Facilitation by a Spiny Shrub on a Rhizomatous Clonal Herbaceous in Thicketization-Grassland in Northern China: Increased Soil Resources or Shelter from Herbivores - Saixiyala,; Yang, Ding; Zhang, Shudong; Liu, Guofang; Yang, Xuejun; Huang, Zhenying; Ye, Xuehua (Frontiers in Plant Science, 2017)
The formation of fertility islands by shrubs increases soil resources heterogeneity in thicketization-grasslands. Clonal plants, especially rhizomatous or stoloniferous clonal plants, can form large clonal networks and use heterogeneously distributed resources effectively. In addition, shrubs, especially spiny shrubs, may also provide herbaceous plants with protection from herbivores, acting as ‘shelters’. The interaction between pre-dominated clonal herbaceous plants and encroaching shrubs remains unclear in thicketization-grassland under grazing pressure. We hypothesized that clonal herbaceous plants can be facilitated by encroached shrubs as a ‘shelter from herbivores’ and/or as an ‘increased soil resources’ under grazing pressure. To test this hypothesis, a total of 60 quadrats were chosen in a thicket-grassland in northern China that was previously dominated by Leymus chinensis and was encroached upon by the spiny leguminous plant Caragana intermediain. The soil and plant traits beneath and outside the shrub canopies were sampled, investigated and contrasted with an enclosure. The soil organic matter, soil total nitrogen and soil water content were significantly higher in the soil beneath the shrub canopies than in the soil outside the canopies. L. chinensis beneath the shrub canopies had significantly higher plant height, single shoot biomass, leaf length and width than outside the shrub canopies. There were no significantly differences between plant growth in enclosure and outside the shrub canopies. These results suggested that under grazing pressure in a grassland undergoing thicketization, the growth of the rhizomatous clonal herbaceous plant L. chinensis was facilitated by the spiny shrub C. intermedia as a ‘shelter from herbivores’ more than through ‘increased soil resources’. We propose that future studies should focus on the community- and ecosystem-level impacts of plant clonality.